Evaluation of Water Channeling Problems and Planning for Its Improvement Using the Remedial Cementing Method and Its Economics in Well AB-30 Field AB PT. Pertamina EP - Deni Kurniawan; KRT Nur Suhascaryo; Boni Swadesi (Journal of Petroleum and Geothermal Technology, 2022)
The AB-30 well is an oil producing well located in the AB Field. Production performance data shows that AB-30 shows excessive water production behavior or is a high water cut production well. In addition, the interpretation of CBL data shows an amplitude value of <10 mV in the productive interval. This condition is an indicator that the primary cementing activity in this well is not good. Therefore, a comprehensive and integrated analytical method is needed to identify the problem of excess water production and to design and plan water shut-off activities through squeeze cementing as an effort to mitigate the problem of high water cut to economic analysis.The research begins by identifying the problem of excess water production, whether caused by water channeling, water coning, changes in water oil contact, or by the physical properties of the reservoir rock. Identification is done through production analysis and water diagnostic plots. The next stage is to evaluate the interpretation of CBL Logging results to strengthen the results of production data analysis. After confirming that the problem of excess water production is caused by poor cement bonding cement, the next step is to calculate the cement work program in order to repair the bad cement bonding. Subsequently, the productive zone interval re-perforation was carried out according to the results of the OH Loh Co Log evaluation. No less important is to conduct an economic analysis as a basis for whether or not this work is feasible.The result of this research is that the water shut-off activity went well and was able to reduce the level of excess water production in the AB-30 well and optimize oil production so as to provide a good economic indicator of oil recovery. Remedial cementing work for bonding repair was carried out at well AB-30. The first work is to close the existing layer, followed by Logging evaluation (CBL-USIT). The evaluation results showed that the cement bonding was good with the CBL amplitude parameter < 10 mV. After that, the productive zone reperforation was carried out. The economy by considering the values of economic indicators such as Pay Out Time and Rate Of Investment showed positive results so that the priority and strategy of well intervention could be continued. The results obtained before the well intervention were 148 BOPD oil production, 97% water cut after well intervention was 880 BOPD average oil production, 0% water cut for 1.5 months